Iron-cobalt photo-thermal catalyst as well as preparation method and application thereof
By preparing iron-cobalt photothermal catalysts, using hydrothermal coprecipitation and high-temperature reduction methods, the problem of low photoenergy utilization of photocatalysts is solved, and the synthesis of catalytic ammonia under mild conditions is achieved, which meets industrial needs and reduces energy consumption.
Patent Information
- Application Number
- CN202411337723.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
AI Technical Summary
The existing photocatalysts have low utilization of light energy and low ammonia production rate under mild conditions, making it difficult to meet industrial needs.
Using the preparation method of iron and cobalt photothermal catalyst, iron and cobalt chloride hexahydrate are dissolved in deionized water, and hydrothermal coprecipitation reaction is carried out to reduce the iron and cobalt in N2/H2 atmosphere at high temperature. The catalyst of two metal active sites achieves efficient use of photoenergy to catalyze the synthesis of ammonia.
It improves the utilization rate of light energy of the catalyst, and can efficiently catalyze nitrogen and hydrogen synthesis ammonia under normal pressure conditions, reduces energy consumption, improves ammonia production efficiency, and can be effectively absorbed and utilized in the ultraviolet-visible-infrared light region.
Smart Images

Figure CN119236938A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to an iron-cobalt photothermal catalyst and a preparation method and application thereof. Background Art
[0002] Ammonia is an indispensable substance in people's production and life. It is widely used in all walks of life and fields of human beings, such as agriculture, chemical industry, manufacturing industry, etc. With the gradual development of human society, human demand for ammonia has gradually increased. At present, the method of catalytic ammonia production and nitrogen fixation in industry is still mainly based on the Haber-Bosch method. The Haber-Bosch method mainly uses coal or natural gas as energy fuel to catalyze the cracking of nitrogen and hydrogen under high temperature and high pressure to synthesize ammonia. Precisely because of its extremely harsh reaction conditions, the Haber-Bosch method has a huge demand and loss for energy, and a large amount of carbon dioxide and other gases will be produced during the reaction process, which pollutes the environment and does not conform to my country's "green" development concept. Therefore, the development of new methods and new materials for catalytic synthesis of ammonia is still a topic of great significance.
[0003] To solve this problem, researchers have introduced new energy sources such as electricity and light into the process of catalytic ammonia production, and developed new methods such as electrocatalysis and photocatalysis to catalyze the synthesis of ammonia under mild conditions. In particular, the photocatalytic method has attracted much attention and in-depth research due to its sustainable energy, easy availability, wide range, and cleanliness. However, there are still many problems to be solved in photocatalytic ammonia production. For example, the ammonia production efficiency is mostly around 100 μmol g -1 catalyst h -1 The order of magnitude is too small to meet the demand for industrial ammonia production; photocatalytic materials have low light energy utilization efficiency and can only absorb ultraviolet light and visible light, but cannot utilize infrared light, which has the highest content in the spectrum, which greatly wastes light energy. Therefore, the development of catalysts that can efficiently utilize solar energy to catalyze the synthesis of ammonia is still a technical challenge. Summary of the invention
[0004] In view of this, the present invention aims to provide a method for preparing an iron-cobalt photothermal catalyst to solve the problems of low light energy utilization rate of existing catalysts and low ammonia production rate under mild conditions.
[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0006] A method for preparing an iron-cobalt photothermal catalyst comprises the following steps:
[0007] 1) dissolving ferric chloride hexahydrate solid in deionized water to obtain a ferric chloride solution;
[0008] 2) dissolving cobalt chloride solid in deionized water to obtain a cobalt chloride solution;
[0009] 3) mixing the ferric chloride solution and the cobalt chloride solution uniformly, then adding ammonia water dropwise while stirring to adjust the pH value of the solution to 9, and then performing a hydrothermal coprecipitation reaction at a certain temperature, and after the hydrothermal coprecipitation reaction is completed, washing, drying, and grinding to obtain an iron-cobalt catalyst precursor powder;
[0010] 4) subjecting the iron-cobalt catalyst precursor powder to a high-temperature reduction reaction in an atmosphere of N2 / H2=1 / 3 to obtain an iron-cobalt photothermal catalyst.
[0011] Optionally, in step 1), the mass ratio of the ferric chloride hexahydrate solid to the deionized water is 1:1.
[0012] Optionally, in step 2), the mass ratio of the cobalt chloride solid to the deionized water is 1:1.
[0013] Optionally, in step 3), the mass ratio of the ferric chloride solution to the cobalt chloride solution is 10-40:1.
[0014] Optionally, the reaction temperature of the coprecipitation reaction in step 3) is 90° C. and the reaction time is 12 h.
[0015] Optionally, the reaction temperature of the high temperature reduction reaction in step 4) is 500° C. and the reaction time is 7 h.
[0016] The second object of the present invention is to provide an iron-cobalt photothermal catalyst, which is prepared by the above-mentioned preparation method of the iron-cobalt photothermal catalyst.
[0017] The third object of the present invention is to provide an application of the above-mentioned iron-cobalt photothermal catalyst in catalyzing the synthesis of ammonia from nitrogen and hydrogen.
[0018] Compared with the prior art, the preparation method of the iron-cobalt photothermal catalyst of the present invention has the following advantages:
[0019] 1. The present invention combines an ammonia coprecipitation reaction method with a high-temperature reduction method to obtain an iron-cobalt photothermal catalyst having two metal active sites, iron and cobalt. The synthesis method is simple and easy, without the need to introduce other substances and excessive synthesis steps. The raw materials are widely available and inexpensive, and are suitable for industrial production.
[0020] 2. The iron-cobalt photothermal catalyst obtained by the present invention is a photoinduced electron transfer catalyst, which can be driven by light to realize photothermal catalytic reaction, and can achieve higher catalytic performance under normal pressure conditions, thereby achieving the purpose of energy saving.
[0021] 3. When the iron-cobalt photothermal catalyst prepared by the present invention is used as a photothermal catalytic ammonia synthesis catalyst, the utilization rate of the catalyst for light energy is improved. It absorbs and utilizes light in the ultraviolet-visible-infrared light region, can convert light energy into heat energy, increase the reaction temperature and thus increase the catalytic ammonia production efficiency of the catalyst; light irradiation can reduce the activation energy of the material, increase the material's ability to activate nitrogen, reduce the reaction order of nitrogen, and thus improve the efficiency of catalytic ammonia production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0023] Figure 1 This is the XRD pattern of the iron-cobalt photothermal catalyst of Example 1 of the present invention;
[0024] Figure 2 The XRD diagram of the pure iron catalyst of Comparative Example 1 of the present invention;
[0025] Figure 3 This is a SEM image of the iron-cobalt photothermal catalyst of Example 1 of the present invention.
[0026] Figure 4 This is a SEM image of the pure iron catalyst of Comparative Example 1 of the present invention;
[0027] Figure 5 The mapping graphs of the iron-cobalt photothermal catalyst of Example 1 of the present invention and the pure iron catalyst of Comparative Example 1 are shown;
[0028] Figure 6 This is a photothermal catalytic performance diagram of the iron-cobalt photothermal catalyst of Example 1 of the present invention;
[0029] Figure 7 The temperature diagram of the iron-cobalt photothermal catalyst of Example 1 of the present invention under different irradiation wavelengths
[0030] Figure 8 The number of active sites of the iron-cobalt photothermal catalyst of Example 1 of the present invention is tested;
[0031] Fig. 9 The catalytic performance of the iron-cobalt photothermal catalyst under light and dark reaction conditions without light of Example 1 of the present invention;
[0032] Fig.10 is the activation energy of the iron-cobalt photothermal catalyst under light and dark reaction conditions without light of Example 1 of the present invention;
[0033] Fig.11 It is the nitrogen reaction order of the iron-cobalt photothermal catalyst under the conditions of light and dark reaction without light in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] In order to enable those skilled in the art to better understand the technical solutions and technical effects of the present invention, several embodiments are provided below. Obviously, what is described below is only an embodiment and does not limit the protection scope of the present invention.
[0035] Example 1
[0036] A method for preparing an iron-cobalt photothermal catalyst comprises the following steps:
[0037] 1) dissolving 100 g of solid ferric chloride hexahydrate in the same amount of deionized water to prepare a 50% ferric chloride solution;
[0038] 2) Take another 20g of CoCl2 solid and put it into a 100mL beaker, add 20mL of deionized water and stir to dissolve, to obtain a cobalt chloride solution with a mass fraction of 50%;
[0039] 3) taking 10 g of the ferric chloride solution obtained in step 1) into a 500 mL beaker, adding 40 mL of deionized water and stirring to dissolve evenly, then adding 0.5 g of the cobalt chloride solution obtained in step 2), stirring to mix evenly, then dropping ammonia water while stirring to adjust the pH of the solution to 9, then transferring to a 90 ° C oven and heating for 12 h for coprecipitation reaction, after the coprecipitation reaction is completed, washing, drying, and grinding to obtain an iron-cobalt catalyst precursor powder;
[0040] 4) The iron-cobalt catalyst precursor powder obtained in step 3) was subjected to a high-temperature reduction reaction at 500° C. for 7 h in an atmosphere of N 2 / H 2 = 1 / 3 to obtain a Fe-5% Co photothermal catalyst.
[0041] The Fe-5%Co photothermal catalyst prepared in this example was exposed to a xenon lamp with an intensity of 6.02 Wcm -2 Under the light condition of , the catalytic ammonia production efficiency of the catalyst was 6200 μmol g -1 catalyst h -1 .
[0042] Example 2
[0043] The difference between this embodiment and embodiment 1 is that the amount of CoCl2 solution used in step 3) is 0.3 g; and the iron-cobalt photothermal catalyst obtained in step 4) is a Fe-3% Co bimetallic catalyst.
[0044] The Fe-3%Co bimetallic catalyst prepared in this example has a -2 Under full-spectrum illumination, the photothermal catalytic ammonia production efficiency of α-Fe material was 5094 μmol g-1 catalyst h -1 .
[0045] Example 3
[0046] The difference between this embodiment and embodiment 1 is that: the amount of CoCl2 solution used in step 3) is 0.7g; and the iron-cobalt photothermal catalyst obtained in step 4) is a Fe-7%Co bimetallic catalyst.
[0047] The Fe-7%Co bimetallic catalyst prepared in this example has a -2 Under full-spectrum illumination, the photothermal catalytic ammonia production efficiency of α-Fe material was 5944 μmol g -1 catalyst h -1 .
[0048] Comparative Example 1
[0049] A method for preparing a pure iron catalyst comprises the following steps:
[0050] 1) dissolving 100 g of solid ferric chloride hexahydrate in the same amount of deionized water to prepare a 50% ferric chloride solution;
[0051] 2) Take 10.812g of the solution obtained in step 1) in a 500mL beaker, add 40mL of deionized water and stir to dissolve evenly, then add ammonia water dropwise while stirring to adjust the pH of the solution to pH=9, then transfer to a 90°C oven and heat for 12h to perform a coprecipitation reaction. After the coprecipitation reaction is completed, wash, dry and grind to obtain a pure iron catalyst precursor powder;
[0052] 3) The pure iron catalyst precursor powder obtained in step 2) is subjected to a high-temperature reduction reaction at 500° C. for 7 h in an atmosphere of N2 / H2=1 / 3 to obtain a pure iron catalyst.
[0053] The pure iron catalyst prepared in this example has a -2 Under full-spectrum illumination, the photothermal catalytic ammonia production efficiency of α-Fe material is 2500 μmol g -1 catalyst h -1 .
[0054] The specific content of Co in the iron-cobalt photothermal catalysts of Examples 1-3 of the present invention and the pure iron catalyst of Comparative Example 1 was determined by ICP-MS detection, as shown in Table 1. Its crystal structure was determined by its X-ray diffraction pattern, as shown in Table 1. Figure 1 and Figure 2 shown.
[0055] As can be seen from Table 1, the iron-cobalt photothermal catalysts obtained in Examples 1-3 of the present invention have all successfully introduced Co, and the content of Co is also consistent with expectations.
[0056] Depend on Figure 1 and Figure 2 It can be seen that since the metal Co introduced in Examples 1-3 of the present invention is in an amorphous state, XRD cannot detect its existence form and crystal form. Therefore, the XRD spectra of the iron-cobalt photothermal catalysts obtained in Examples 1-3 of the present invention and the pure iron catalyst obtained in Comparative Example 1 are the same, and are completely consistent with the standard card JCPDF-060696 of metallic iron, and their XRD diffraction peaks are sharp and have high crystallinity.
[0057] Table 1
[0058] catalyst Theoretical value of iron (ppb) Theoretical value of Co (ppb) Fe measurement value (ppb) Co measurement value (ppb) α-Fe 100 0 130.794 0.000 Fe-3%Co 97 3 87.388 2.405 Fe-5%Co 95 5 86.983 4.253 Fe-7%Co 93 7 84.074 5.221
[0059] The SEM images of the iron-cobalt photothermal catalyst of Example 1 of the present invention and the pure iron catalyst of Comparative Example 1 are as follows: Figure 3 and Figure 4 shown.
[0060] Depend on Figure 3 and Figure 4 It can be seen that the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention has a cubic morphology, which is similar to the appearance of the pure iron catalyst prepared in Comparative Example 1 ( Figure 4 ), there is no obvious difference, and no segregated Co nanoparticles are observed, indicating that the addition of Co has no obvious effect on the morphology and structure of the catalyst material.
[0061] The mapping spectra of the iron-cobalt photothermal catalyst of Example 1 of the present invention and the pure iron catalyst of Comparative Example 1 are as follows: Figure 5 shown.
[0062] Depend on Figure 5 It can be seen that the Co and Fe elements of the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention are uniformly distributed, and the Fe and Co metals coexist in the catalyst, and it is speculated that an alloy is formed, which is consistent with the XRD test results. The above results show that the present invention successfully synthesized a uniform crystalline iron-cobalt photothermal catalyst and its morphology and structure are almost the same as those of pure iron material without the addition of Co element.
[0063] The application of the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention in photothermal catalytic synthesis of ammonia is as follows:
[0064] 20 mg of catalyst was placed in the reactor and the total gas flow rate was 60 mL min -1 The catalytic reaction was carried out under the gas conditions of N2:H2=1:3, and the intensity of the xenon lamp was 6.02Wcm -2The generated ammonia gas was then absorbed by dilute sulfuric acid, and the content of ammonium ions in the dilute sulfuric acid solution was detected by ion chromatography. The catalytic ammonia production performance of the catalyst under this condition was found to be 6200 μmol g -1 catalyst h -1 ( Figure 6 ).
[0065] By adding a cutoff filter to adjust the wavelength of the xenon lamp irradiating the catalyst, the catalytic performance of the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention in synthesizing ammonia under visible-infrared and infrared light irradiation was tested. Figure 6 shown.
[0066] Depend on Figure 6 It can be seen that under the irradiation of ultraviolet-visible-near infrared light of >450nm and >700nm, the ammonia production efficiency of the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention is 3735 and 2424 μmol g -1 catalyst h -1 Even under near-infrared light irradiation of >800nm, the catalyst still has excellent catalytic performance for synthesizing ammonia, and its ammonia production performance can still reach 518μmol g -1 catalyst h -1 This shows that the iron-cobalt photothermal catalyst prepared by this method has a high utilization rate of light energy, can better catalyze the reaction, and is a good photothermal ammonia synthesis catalyst.
[0067] By adding a cutoff filter to adjust the wavelength of the xenon lamp irradiating the catalyst, the reaction temperature of the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention under visible-infrared and infrared light irradiation was tested. Figure 7 shown.
[0068] Depend on Figure 7 It can be seen that the reaction temperature of the iron-cobalt photothermal catalyst reached 508°C under full-spectrum light irradiation conditions, and the reaction temperature of the catalyst also reached 433°C and 416°C under ultraviolet-visible-near-infrared light irradiation of >450nm and >700nm, and even the reaction temperature of the catalyst could reach 359°C under near-infrared light irradiation of >800nm. This further illustrates that the iron-cobalt photothermal catalyst prepared by this method has a high light energy utilization rate, can convert light into heat energy very well, and then promote the reaction process of nitrogen-hydrogen synthesis of ammonia, achieving the purpose of green catalysis and energy saving.
[0069] After the catalyst was reduced normally, nitrogen was introduced alone to allow the reaction sites on the catalyst surface to fully adsorb nitrogen. Then, hydrogen was introduced at room temperature to discharge excess nitrogen. The temperature was then gradually raised to 500° C. The ammonia production was tested to determine the nitrogen adsorption amount and the number of reaction sites of the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention. The results are shown in FIG. Figure 8 shown.
[0070] Depend on Figure 8 It can be seen that the amount of nitrogen adsorbed by the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention is much higher than that of the pure iron catalyst, indicating that the introduction of Co increases the number of catalyst reaction sites, thereby greatly improving the catalytic performance of the catalyst.
[0071] In order to explore the effect of photoactivation on the photothermal ammonia synthesis process, the catalytic performance of Fe-Co photothermal catalysts in the light and no light conditions was compared at 500 °C. The results are as follows: Fig. 9 shown.
[0072] Depend on Fig. 9 It can be seen that the catalytic ammonia production efficiency of the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention under no light conditions is 3090 μmol g -1 catalyst h -1 The catalytic ammonia production efficiency under light-added conditions reached 6516 μmol g -1 catalyst h -1 It can be seen that the iron-cobalt photothermal catalyst can use light to drive the catalytic production of ammonia, thereby greatly improving the catalytic ammonia production efficiency of the catalyst.
[0073] In order to further illustrate the effect of light on the catalytic ammonia production process of the catalyst, the activation energy of the iron-cobalt photothermal catalyst prepared in Example 1 of the invention was tested under light and no light conditions. The results are as follows: Fig.10 shown.
[0074] Depend on Fig.10 It can be seen that the activation energy of the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention under no light conditions is 108.1 kJ mol -1 , the activation energy under light conditions is 77.9 kJ mol -1 After illumination, the activation energy decreased significantly, indicating that illumination reduced the difficulty of catalyzing nitrogen and hydrogen to ammonia synthesis by the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention, and affected the process of catalytic ammonia production.
[0075] In order to study the effect of light on the reaction process of nitrogen-hydrogen synthesis of ammonia, a comparative test of the nitrogen light reaction order of the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention was conducted at 400°C. The results are as follows: Fig.11 shown.
[0076] Depend on Fig.11 It can be seen that the nitrogen reaction order of the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention without light is 1.43, and the nitrogen reaction order of the iron-cobalt photothermal catalyst after light irradiation is 0.43, which has decreased significantly, indicating that light irradiation can greatly accelerate the step of nitrogen dissociation, thereby improving the efficiency of catalytic ammonia production.
[0077] The above experimental data prove that the iron-cobalt photothermal catalyst prepared in Example 1 of the present invention has a larger number of reaction sites, has a very high efficiency in photothermal catalytic synthesis of ammonia, and has a strong utilization rate of light energy. It is a photothermal catalytic synthesis of ammonia catalyst that can be used for industrial catalytic synthesis of ammonia.
[0078] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an iron-cobalt photothermal catalyst, characterized in that: The following steps are involved: 1) dissolving ferric chloride hexahydrate solid in deionized water to obtain a ferric chloride solution; 2) dissolving cobalt chloride solid in deionized water to obtain a cobalt chloride solution; 3) mixing the ferric chloride solution and the cobalt chloride solution uniformly, then adding ammonia water dropwise while stirring to adjust the pH value of the solution to 9, and then performing a coprecipitation reaction at a certain temperature, and after the coprecipitation reaction is completed, washing, drying, and grinding to obtain an iron-cobalt catalyst precursor powder; 4) subjecting the iron-cobalt catalyst precursor powder to a high-temperature reduction reaction in an atmosphere of N2 / H2=1 / 3 to obtain an iron-cobalt photothermal catalyst.
2. The method for preparing the iron-cobalt photothermal catalyst according to claim 1, characterized in that: In step 1), the mass ratio of the ferric chloride hexahydrate solid to the deionized water is 1:
1.
3. The method for preparing the iron-cobalt photothermal catalyst according to claim 1, characterized in that: In step 2), the mass ratio of the cobalt chloride solid to the deionized water is 1:
1.
4. The method for preparing the iron-cobalt photothermal catalyst according to claim 1, characterized in that: In step 3), the mass ratio of the ferric chloride solution to the cobalt chloride solution is 10-40:
1.
5. The method for preparing the iron-cobalt photothermal catalyst according to claim 1, characterized in that: Step 3) The reaction temperature of the coprecipitation reaction is 90° C. and the reaction time is 12 h.
6. The method for preparing the iron-cobalt photothermal catalyst according to claim 1, characterized in that: The reaction temperature of the high temperature reduction reaction in step 4) is 500° C. and the reaction time is 7 h.
7. An iron-cobalt photothermal catalyst, characterized in that: The invention is prepared by the preparation method of the iron-cobalt photothermal catalyst according to any one of claims 1 to 6.
8. Use of the iron-cobalt photothermal catalyst according to claim 7 in catalyzing the synthesis of ammonia from nitrogen and hydrogen.
